Influence of Xanthan Gum Addition on Frozen Starch Paste Properties - Ferrero, Cristina (1994)
The effect of freezing rate, storage temperature (-5 to -20°C) and gum addition (0.3 % w/w) on corn starch and wheat flour pastes (10 % w/w) was studied to analyze various aspects: rheological behavior, exudate production, ice recrystallization by indirect microscopic observation and amylopectin retrogradation by Differential Scanning Calorimeter (DSC). High freezing rates produced a higher paste quality due to smaller ice crystals formation and the absence of starch retrogradation. During frozen storage, starch retrogradation and ice recrystallization contributed to the deterioration of the system (spongy structure, decrease of apparent viscosity and increase of exudate production). The addition of xanthan gum improved system stability. Exudate production decreased and original rheological properties were maintained. No effect of hydrocolloid addition was observed on ice crystal sizes. DSC analysis showed that xanthan gum does not modify amylopectin retrogradation.